2021
DOI: 10.3390/pr9060920
|View full text |Cite
|
Sign up to set email alerts
|

New Analytical Method for Determination of Phthalates in Wastewater by on Line LC-GC-MS Using the TOTAD Interface and Fraction Collector

Abstract: There is an increasing demand for automatic, reliable and sensitive analytical methods for determining trace levels of phthalic acid esters (PAEs) in environmental samples. While on line coupled liquid chromatography-gas chromatography (LC-GC) has been proof to be a powerful tool for trace-level analyses in complex matrices, the present work presents a new totally automated on line LC-GC method, using the Through Oven Transfer Adsorption Desorption (TOTAD) interface, for the analysis of four of the main phthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…LC-GC is frequently employed for the analysis of various analytes in both wines and olive oils [141,142]. However, concerning the analysis of phthalates using LC-GC, one can only find applications to water samples [143,144]. To date, to the best of our knowledge, no studies have been found that apply it to the analysis of phthalates in olive oil and wine.…”
Section: Liquid Chromatographymentioning
confidence: 99%
“…LC-GC is frequently employed for the analysis of various analytes in both wines and olive oils [141,142]. However, concerning the analysis of phthalates using LC-GC, one can only find applications to water samples [143,144]. To date, to the best of our knowledge, no studies have been found that apply it to the analysis of phthalates in olive oil and wine.…”
Section: Liquid Chromatographymentioning
confidence: 99%